'One big club of which we are all members': management and work culture in New Zealand department stores, c. 1910–1960. Issue 1 (2nd January 2021) - Roberts, Evan
ABSTRACT: This paper examines the work and work culture of department store salespeople in New Zealand department stores. Following the management advice of American, British, and Australian experts New Zealand store managers cultivated the notion of a store family and imported welfare work practices aimed at creating happy employees and a culture of consumption and modernity. The organization of New Zealand department stores was formally similar to those in the United States and Australia, but most stores were smaller with fewer than 500 employees. Departments in New Zealand stores were smaller and the role of buyers as department managers was attenuated. In this setting the efforts of management to cultivate a store family and a workplace social life that spanned departments were successful.